2021
DOI: 10.1007/s00436-021-07122-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhipicephalus microplus and its vector-borne haemoparasites in Guinea: further species expansion in West Africa

Abstract: Rhipicephalus microplus is an ixodid tick with a pantropical distribution that represents a serious threat to livestock. West Africa was free of this tick until 2007, when its introduction into Benin was reported. Shortly thereafter, the further invasion of this tick into West African countries was demonstrated. In this paper, we describe the first detection of R. microplus in Guinea and list the vector-borne haemoparasites that were detected in the invader and indigenous Boophilus species.In 2018, we conducte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…bigemina in Mexican livestock ovaries and a mummified foetus in Veracruz. These findings are not surprising given that both groups of pathogens are transmitted by the same vector, the cattle tick Rhipicephalus microplus [13]. According to the histopathological results, it is important to mention that the pathophysiology of these pathogens caused infertility [8].…”
Section: Resultsmentioning
confidence: 97%
“…bigemina in Mexican livestock ovaries and a mummified foetus in Veracruz. These findings are not surprising given that both groups of pathogens are transmitted by the same vector, the cattle tick Rhipicephalus microplus [13]. According to the histopathological results, it is important to mention that the pathophysiology of these pathogens caused infertility [8].…”
Section: Resultsmentioning
confidence: 97%
“…clone Tajikistan sequences KJ930191 and KJ930192 obtained from Hyalomma anatolicum from Tajikistan [ 25 ]; 91.7% identity with sequences MW054555 and MW054557 deposited for Ehrlichia sp. isolate YNT obtained from Rhipicephalus annulatus and Rhipicephalus geigyi from Guinea [ 26 ] was also found. In addition, the nucleotide sequences at the 16S rRNA partial gene showed a percentage identity ranging from 99.4 to 99.7% when compared to several deposited sequences of uncultured Ehrlichia spp .…”
Section: Resultsmentioning
confidence: 99%
“…T. annulata can be found in both erythrocytes and lymphocytes of their host and is transmitted by ticks of Hyalomma (H. anatolicum anatolicum, H. anatolicum excavatum, H. detritum and H. marginatum marginatum (Sayin et al, 2003). B. bigemina is presently considered as one of the most important constraints in production of livestock and transmitted by Rhipicephalus ticks (Makenov et al, 2021) and mainly infects the red blood cells (Ristic, 1981). A. marginale is caused by a group of obligate intracellular bacteria and are transmitted by Rhipicephalus ticks (Yan et al, 2020;Galay et al, 2021), and observed within erythrocytes (Jurkovic et al, 2020).…”
Section: Phylogenetic Studiesmentioning
confidence: 99%